Improving the Quality of Postoperative Recovery of Elderly and Senile Patients with Circulatory Insuficiency (Perioperaciina Medicina, 2024)
A comparison of prolonged epidural analgesia (PEA) with conventional on-demand analgesia in geriatric patients with circulatory insuffi ciency (CI) who underwent surgery on the lower extremities demonstrated a pronounced opioid-sparing effect in them in the postoperative period. PEA in the postoperative period is indicated mainly in elderly and senile patients with limited cardiovascular system reserves, as epidural anaesthesia signifi cantly reduces the risk of cardiac complications in this patient population.
Keywords: elderly and senile age; prolonged epidural anesthesia; postoperative analgesia; heart failure